Effects of neuromuscular electrical stimulation on masticatory muscles in elderly stroke patients - Wang, Joong-San; Lee, Ju-Hwan; Kim, Nyeon-Jun (Journal of Physical Therapy Science, 2015)
[Purpose] This study aimed to examine the effects of neuromuscular electrical stimulation on masticatory muscle activation in elderly stroke patients. [Subjects and Methods] The subjects included 20 elderly patients diagnosed with stroke and 10 healthy elderly individuals. The neuromuscular electrical stimulation group received stimulation on the masseter muscle in the affected side for 30 min each day, 3 times per week for 8 weeks. In all the subjects, surface electromyography was used to measure activity of the masseter and temporal muscles in both sides under resting and clenching conditions. [Results] In the neuromuscular electrical stimulation group, after the intervention, an increase in the activity of all of the masticatory muscles was observed during clenching, with a significant increase in the activity of the masseter muscle in the affected side. Significant differences between the groups were not observed after the interventions. [Conclusion] The results of this study suggest that application of neuromuscular electrical stimulation effectively improves muscle activity in elderly stroke patients during clenching, and that this technique can be applied particularly for the improvement of the clenching activity of the masseter muscle in the affected side.